Analisis kesesuaian soal hots berdasarkan susunan taksonomi bloom pada buku siswa kelas V SD tema 2 mata pelajaran IPS kurikulum 2013 - Qory Khafidhoh Ayunta; Hadi Mulyono; Fadhil Purnama Adi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
Education starts from elementary school, where we will learn various kinds of subjects, one of which is social science, with social science learning (IPS) it will be easier for someone to understand social problems and know how to overcome them. However, it will be difficult if students are not trained to use questions that do not provide a stimulus to solve problems, so it is very necessary to practice questions based on HOTS (Higher Order Thinking Skills) because it will provide the experience that students need to think critically, criticize, and develop their potential